STABILITY OF SULFATE-SODALITE (NOSEAN) UNDER HYDROTHERMAL CONDITIONS - Kotel'nikov A.R.; Romanenko I.M.; Suk N.I.; Gurbanov A.A.; Kotel'nikova Z.A. (My University, 2004)
The nosean (Na8Al6Si6O24SO4) stability was studied under hydrothermal conditions at 1-3 kbars as a function of salt content in the solution and temperature. The sodalite (nosean)-nepheline relationship is controlled by the univariant reaction: Na8Al6Si6O 24(SO4) = 6NaAlSiO4 + Na 2SO4. It was shown that this reaction depends also on the phase state of the fluid. Nosean is stable at the following Na2SO4 contents in the mineral-forming fluid: ≥2 wt % (600°C), ≥1 wt % (700°C), and ≥5 wt % (800°C). Based on the stability of end members of the (Cl,S -sodalite solid solution, an equation was derived to determine the salt content in the mineral-forming fluid from the composition of natural sodalites: C (wt %) = (255 - 214.3 × X) + (-330 + 270 × X) × (1000/T) + (107.4 - 85 × X) × (1000/T)2, where X is the sulfur mole fraction in sodalite, X = S/(Cl + S); T is temperature, K. The sodalite-bearing assemblages of the Lovozero alkaline massif were studied. Their formation temperatures were determined to be between 910 and 400°C, and salt contents in the mineral-forming fluids were estimated using sodalite compositions.